PENGARUH WAKTU PENYERBUKAN TERHADAP KUALITAS HASIL TANAMAN MELON (Cucumis melo L) DENGAN PERKAWINAN SILANG TANAMAN SEMANGKA (Citrullus vulgaris L) - Widodo, Adik Sugeng; As'ari, Hasyim; Kurnia, Tristi Indah Dwi; Novitasari, Amanda (JURNAL BIOSENSE, 2024)
Decreased production of melon (Cucumis melo L) which is due to constraints in fruit quality decreases due to the ability of fruit formation is naturally low due to a failure in the process of pollination. The success of pollination it self is influenced by the maturity of the male flowers and female flowers itself. Therefore we need a suitable time to perform pollination to see the stigma receptivity and pollen viability at the same level. To overcome these problems need to develop crops melon (Cucumis melo L) through the technique of cultivation is called plant breeding to obtain the production of melon (Cucumis melo L) qualified by determining the time of pollination and crossed with a watermelon (Citrullus vulgaris L). This research is experimental research design using a randomized block design (RAK) 1 factor with 5 treatment combinations and each treatment using 10 replications. The treatment factors are as follows: PA = at 05:00 to 06:00, PB = at 07:00 to 08:00, PC = at 09:00 to 10:00, PD = at 11 : 00 to 12:00 and PE = at 13:00 to 14:00. The data were collected and presented in tables and statistical analysis of test One-Way ANOVA (Analysis Of Variance). If there is a real difference followed by testing of LSD (Least Significant Difference) (p <0.05). Statistical analysis One-Way ANOVA test and LSD show that there is the influence of pollination time on the fruit weight, average fruit diameter and weight of seed resulting from cross-breeding melon (Cucumis melo L) and watermelon (Citrullus vulgaris L). Data show that the PA treatment is the best treatment compared with other treatments. This happens Because the quality of pollen in the morning are of better quality compared to during the day so that pollen powderd in the morning better able to fertilize the pistil to the maximum.